William James über religiöse Erfahrung - Ricken, Friedo (Zeitschrift für katholische Theologie, 2009)
Kant defined knowledge through the two equal elements of Eindrücke and Begriffe, which link the immediate experiences or Eindrücke with objects and thus create order. In his reception of Kant W. James formulated a radical pragmatism in which Kant's Begriffe assume secondary importance. According to James, associations of experience with objects and the resulting sense of order are themselves an experience of the senses. The subjective, therefore, enjoys precedence over the objective order. What follows is a critical examination of James' application of this theory towards religious experience.